Answer:
x = -7
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Explanation:
Step 1: Define Equation
-(5 - 8x) + 4x = -89
Step 2: Solve for x
- Distribute negative: -5 + 8x + 4x = -89
- Combine like terms: -5 + 12x = -89
- Isolate x term: 12x = -84
- Isolate x: x = -7
Step 3: Check
Plug in x into the original equation to verify it's a solution.
- Substitute in x: -(5 - 8(-7)) + 4(-7) = -89
- Multiply: -(5 + 56) - 28 = -89
- Add: -61 - 28 = -89
- Subtract: -89 = -89
Here we see that -89 does indeed equal -89.
∴ x = -7 is the solution to the equation.